Using behavioral strategies to cope with the threat of terrorism: a national-level study - Sloan, Melissa M. (Crime & delinquency, 2021)
Although the risk of dying in a terrorist attack in the United States is almost non-existent, recent polls indicate that Americans rank terrorism as a top national concern, prioritizing it over other issues such as the economy, health care, and the environment. The current study examines how Americans are impacted by the threat of terrorism today. Analyses of original national survey data suggest that Americans currently engage in behavioral coping in response to the threat of terrorism, and their coping responses vary by levels of worry about terrorism, political orientation, emotional vulnerability, and the association that they make between Muslims and terrorism. The observed behavioral adaptations have implications for community engagement, the economy, and psychological well-being on an individual level.